Matrizes ideológicas dos arcebispos paulistanos (1956-85): um olhar sob o prisma do semanário O São Paulo - Lanza, Fabio (2006)
The research focused on the Catholic Church archbishops acting in the archdiocese of São Paulo from 1956 to 1985, based on the analysis of O São Paulo. The work aimed a historical and sociological orientation based on documents and interviews. The initial point is the ideology used by the archbishops Dom Agnelo Rossi e Dom Paulo Evaristo Arns revisiting the prior period, Dom Carmelo V. Motta, head of the Fundação Metropolitana Paulista, responsible for the journal O São Paulo. The documental sources were based on historical documents about the Paulistana Church, and the publications of O São Paulo, privileging the articles and the editorials; using different authors to analise their contents. The oral sources were constituted on the subjetcs, which were selected using criteria based on the Oral History, using the personal experience inside the Clergy and their relationship with the MCS from the Archidiocese of São Paulo. The emeritus archbishop cardinal Dom Paulo Evaristo Arns, father Antônio Aparecido Pereira, monk Carlos Josaphat, Prof. Dr. Fernando Altemeyer, Dom Angélico Bernardino Sândalo, Dom Antônio Celso de Queiroz and Dom Benedicto Ulhôa Vieira were interviewed following a script based on the problems of the research. Depending on the historial and sociological period analysed, the Catholic Church was a collective body that expressed different ideologies, according to the documental and oral sources. The Catholic Church of São Paulo by its weekly publication expressed different speeches that made evident the drastic changings that took place during the 1960 s and 1970 s, associated to inner and outer factors of the intitutional structure. We can see that there is a link on the different phases and contexts, based on the ecclesiastic mission and the religious project, defined as an ideal that does not characterize itself as neither a political, nor an economy system. The cardinal Arns conduct, started during the 1970 s, propagated through the O São Paulo an ideal, centered on the maintenance of truth, justice, political and religious freedom, social organizations participation and the commitment of The Catholic Church to the extreme defense of man